Optimal Taxation of Married Couples with Household Production - Henrik Jacobsen Kleven; Klaus Thustrup Kreiner (University of Copenhagen, Economic Policy Research Unit (EPRU), 2004)
The literature suggests that the concern for economic efficiency calls for individual-based taxation of married couples with a higher rate on the primary earner. This paper reconsiders the choice of tax unit in the Becker model of household production. Our aim is to study the robustness of previous results to the modelling of time allocation. In addition, we analyze the interaction between the optimal income tax for couples and the chosen commodity tax structure. In the absence of restrictions on the use of commodity taxes, efficient taxation requires joint taxation of the family. In the presence of restricted commodity taxation, the income tax should compensate for the erroneous commodity taxes. In this case, individual taxation is typically optimal, but not necessarily with a higher rate on primary earners as usually suggested.
Keywords: H21; D13; J22; 330; Familienbesteuerung; Optimale Besteuerung; Haushaltsproduktion